A Longitudinal Analysis of Weight Changes before and after Total Knee Arthroplasty: Weight Trends, Patterns, and Predictors - Oyem, Precious C.; Rullán, Pedro J.; Pasqualini, Ignacio; Klika, Alison K.; Higuera, Carlos A.; Murray, Trevor G.; Krebs, Viktor E.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2024)
Longitudinal data on patient trends in body mass index (BMI) and the proportion that gains or loses significant weight before and after total knee arthroplasty (TKA) are scarce. This study aimed to observe patients longitudinally for a 2-year period and determine (1) clinically significant BMI changes during the 1 year before and 1 year after TKA and (2) identify factors associated with clinically significant weight changes.A prospective cohort of 5,388 patients who underwent primary TKA at a tertiary health care institution between January 2016 and December 2019 was analyzed. The outcome of interests was clinically significant weight changes, defined as a ≥5% change in BMI, during the 1-year preoperative and postoperative periods, respectively. Patient-specific variables and demographics were assessed as potential predictors of weight change using multinomial logistic regression.Overall, 47% had a stable weight throughout the study period (preoperative: 17% gained, 15% lost weight; postoperative: 19% gained, 16% lost weight). Patients who were older (odds ratio [OR] = 0.95), men (OR = 0.47), overweight (OR = 0.36), and Obese Class III (OR = 0.06) were less likely to gain weight preoperatively. Preoperative weight loss was associated with postoperative weight gain 1 year after TKA (OR = 3.03). Preoperative weight gain was associated with postoperative weight loss 1 year after TKA (OR = 3.16).Most patients maintained a stable weight before and after TKA. Weight changes during the 1 year before TKA were strongly associated with reciprocal rebounds in BMI postoperatively, emphasizing the importance of ongoing weight management during TKA and the recognition of patients at higher risk for weight gain.Level of evidence II (prospective cohort study).
Keywords: TKA; BMI; weight change; weight trend; predictors